Online Gaming Addiction as A Predictor of Sleep Quality through Male Teenagers - Apriyeni, Emira; Patricia, Helena; Sandra, Rhona; Yanti, Etri (PT. Riset Press International, 2025)
About 18% of the world's population, especially teenagers, had sleep issues in 2023, according to WHO statistics. Addiction to internet gaming is one of the causative factors; it stimulates the Reticular Activating System (RAS), which excites the brain and delays the onset of sleep. In 2024, the current study also sought to find out the association between male teenage students of SMKN 1 Padang City's addiction towards online games and sleep quality. A cross-sectional analytical study was conducted from June until July, 2024. The entire 355 male second-grade students who were chosen by the total sampling technique were considered to be the population. Spearman correlation test was a bivariate and univariate technique used in data analysis. Mean score for sleep quality was 27.54, while that of gaming addiction was 37.44. Spearman test revealed a significant correlation (p = 0.000; ρ = 0.758). It is concluded that there is a strong correlation between online gaming addiction and sleep quality. It is recommended that school education programs on sleep hygiene and time management be provided.